Interaction of Nisin with Anionic Membranes: Purification and Raman Study - Sosa Morales, Marcelo Clemente (2013)
Nisin is an antibiotic peptide ribosomally sintetized by Lactococcus lactis that inhibits the growth of a wide range of gram-positive bacteria. It has a net positive charge (+5) and its weight is approximately 3kDa. Commercially, it is available as a lyophilized powder containing 2.5% (w/w) nisin. Purification was carried out using chromatographic methods. The bactericidal activity of fractions obtained was visualized on agar plates. In addition, Tricine SDS-Page and Mass Spectrometry were performed to confirm the purity of nisin. Raman Spectroscopy was used to study the interaction of this small peptide with anionic models membranes. We evaluated and interpretated signal spectral changes considered specific markers of the lipid packaging, the number of conformers gauche in the hydrocarbon chains and the degree of hydration of the polar heads. For this purpose, dipalmitoylphosphatidylglycerol (DPPG) and dilauroylphosphatidylglycerol (DLPG) were utilized. Measurements were made at room temperature. Analysis of DPPG/Nisin and DLPG/Nisin systems will allow us to know if lipid phase state impact on the interaction and hence to have a better understanding about the action mechanism of nisin.